HIGH-RESOLUTION SEDIMENTARY RECORD IN A NEW BDP-99 CORE FROM POSOL'SK BANK IN LAKE BAIKAL - Bezrukova E.; Bukharov A.; Bychinsky V.; Colman S. (My University, 2004)
Another BDP drilling experiment was carried out in the winter of 1999 at 52degrees05'23"N-105degrees50'24" E, under 201 in of water, on the slope of the Posol'sk Bank, a submerged bottom rise in South Baikal. The -350 m core spanning 1.2-1.3 myr is composed of alternating diatomaceous mud and glacial clays. Diatom stratigraphy and paleomagnetic data show a ca. 200 kyr deposition gap at 134 m, though the core contains the complete Brunhes chron of direct polarity (0-780 kyr). This unconformity, discovered for the first time in the Baikal cores, is direct evidence for tectonic activity in the Selenga region between 0.820 and 1 myr, during the uplift of the Primorsky Ridge inferred from land data. The diatom record in the core correlates well with the marine oxygen isotope stratigraphy and indicates climate-driven variations in diatom production. High-resolution pollen records spanning an interval from 0 to 130 kyr provide a clue to climate change in the Baikal region and Transbaikalia. Correlation of the BDP core and seismic profiling data allows age referencing of the seismoacoustic units and reflections which can be extrapolated onto a large area of the Posol'sk Bank and the shallow-water region near the Selenga Delta. The obtained results shed light on the Pleistocene climate history in the region and the geological history of the Baikal rift.
Keywords: Deep drilling; Lake Baikal; bottom sediments; lithology; sedimentation; seismic profiles; paleoclimate; paleomagnetism; deposition gap; diatom and pollen stratigraphy